Estimating the Epidemiology and Quantifying the Damages of Parental Separation in Children and Adolescents - Arce Fernández, Ramón (Frontiers in psychology, 2016)
The authors disclosed receipt of the following financial support for the research, authorship, and/or publication of this article. This research was funded by the project with reference PI12/00604 (Instituto de Salud Carlos III, Spanish Ministry of Economy and Competitiveness)S